SISTEM INFORMASI PENJUALAN PETI MATI BERBASIS WEB DI CV. GEOJAYA NUSANTARA - Joko Priono Nababan; Wulan Dari (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2022)
Abstract—Sales is an activity that connects customers with sellers through a product or service offered to produce something that is mutually beneficial for both parties. So for that we need a system so that sales transactions can run effectively and efficiently, for example by using a sales information system. CV. Geojaya Nusantara is a company engaged in the sale of coffins. The existing sales system in CV. Currently, Geojaya Nusantara is still carried out conventionally, such as customers who want to buy their products via phone calls or also through messaging applications such as the WhatsApp application. Then the incoming sales data is still done manually, as recorded in a sales book. Therefore, with these problems, a web-based application is needed to support the sales system which aims to simplify all transaction processes, because it can be done anytime and anywhere. The research method used is by conducting direct observations and interviews with employees or shop owners. As for the software development method used is the waterfall method and the programming language used in making the website itself is PHP, HTML, CSS, and JQuery, and for the database it uses MySQL. The expected results in this web-based coffin sales information system at CV Geojaya Nusantara, are expected to be a solution to overcome the problems encountered due to the conventional system, and can also overcome errors in the sales recording input process. Keywords: coffin sales, information system, web-based